2008
DOI: 10.1007/s10815-008-9286-2
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 and VEGF immunopositivity in seminiferous tubule germ cells in cases of obstructive and non-obstructive azoospermia in smokers versus non-smokers

Abstract: Purpose To investigate immunostaining pattern of caspase-3, an apoptosis marker, and vascular endothelial growth factor (VEGF), an hypoxia marker in testis biopsy specimens collected either from smoking or non-smoking patients with azoospermia. Methods Testis biopsy specimens were obtained from thirty seven non-smoker and thirty eight smoker patients. Using immunochemistry technique, caspase-3 and VEGF were evaluated in all intratubular spermatogenic and interstitial Leydig cells.Result(s) Caspase-3 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…VEGF also facilitates the transport of hormones and nutrients and oxygen. (Kilic et al., ; Sisman et al., ) Tunckiran et al. () showed that VEGF administration reduced apoptosis in testicular germ cells.…”
Section: Discussionmentioning
confidence: 98%
“…VEGF also facilitates the transport of hormones and nutrients and oxygen. (Kilic et al., ; Sisman et al., ) Tunckiran et al. () showed that VEGF administration reduced apoptosis in testicular germ cells.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, we found the activation of caspase-9 and caspase-3 was obviously enhanced by VEGFR3 knockdown. As an important apoptosis regulator, Caspase-3 was highly expressed in germ cells of maturation arrest patients [62]. Caspase-3 was processed by cleaved Caspase-9 and hydrolyzed into activated fragment which were responsible for the proteolytic cleavage of the nuclear enzyme poly (ADP-ribose) polymerase (PARP) [63].…”
Section: Discussionmentioning
confidence: 99%
“…Slides were examined without any randomising in their orientation and determinations of immune positive cells were applied as described previously. 27,28 The unbiased counting frame-fractionator combination is a stereological method for counting cells in tissue sections. Cells were counted using a 40x Apo objective for accurate recognition (Figure 1).…”
Section: Stereological Analysismentioning
confidence: 99%